2002
DOI: 10.1145/604596.604597
|View full text |Cite
|
Sign up to set email alerts
|

Literature-based discovery on the World Wide Web

Abstract: Previous research has shown that researchers can generate medical hypotheses by using computers to analyze several, seemingly unrelated, medical literatures. In this work we suggest broader application for the ideas of literature-based discovery. Specifically, we suggest that literature-based discovery can be fruitful in areas other than medicine; that in addition to finding "cures" for "problems," literature-based discovery offers the possibility of finding new problems for existing technologies; that the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 16 publications
0
42
0
1
Order By: Relevance
“…2.1. Etat de l'art : Gordon et Lindsay, qui avaient simulé les expériences de Swanson ont travaillé sur l'utilisation d'Internet dans un système de découverte de connaissances [Gordon, 2002]. Ils proposent de généraliser le modèle utilisé dans le domaine biomédical en un modèle ouvert pour la découverte de connaissances au sens large.…”
Section: Transposition De La Découverte De Connaissances Au Monde Du unclassified
“…2.1. Etat de l'art : Gordon et Lindsay, qui avaient simulé les expériences de Swanson ont travaillé sur l'utilisation d'Internet dans un système de découverte de connaissances [Gordon, 2002]. Ils proposent de généraliser le modèle utilisé dans le domaine biomédical en un modèle ouvert pour la découverte de connaissances au sens large.…”
Section: Transposition De La Découverte De Connaissances Au Monde Du unclassified
“…For example, Gordon and Lindsay (1996, 1998, 2001 used tf * idf to extract concepts from texts. Moreover, UMLS and MeSH are widely used as the semantic tool to identify concepts.…”
Section: Related Researchmentioning
confidence: 99%
“…A related field called Literature-based discovery (LBD) concerns methods for identifying unknown relationships in data drawn from published results [5]. By bringing together results published in several papers, new relationships that were not considered in the original studies can be found.…”
Section: Related Researchmentioning
confidence: 99%